Analysis Of Critical Thinking Ability Physics Education Students to Solve Geometrical Optics Problems - Sarah Octaviana; Abdul Hamid; Elisa Kasli (Asian Journal of Science Education, 2020)
This research was conducted aiming to determine the critical thinking skills of Teacher Training and Education Department Syiah Kuala University physics students based on critical thinking indicators in solving optical geometry problems. This research uses a quantitative approach with descriptive research methods. The population of this research is the 2016 Physics Education students as many as 57 students with 40 students as a sample of respondents. Data collection was performed using a test consisting of 5 essay questions that have been validated for use as an instrument for critical thinking tests. The data obtained is then averaged per indicator and then presented and then categorized using the criteria table for critical thinking skills. The results show the average percentage of values obtained by students in solving optical geometry problems for each critical thinking ability is 43% in the ability to provide an explanation simple, 33% in the ability to build basic skills, 25% in the ability to conclude, 33% in the ability to provide further explanation, and 13% in the ability to formulate strategies and tactics. Based on these results it can be concluded that the critical thinking ability of students based on each indicator in the physics education student at Teacher Training and Education Department Syiah Kuala University is still low.